Interests in the Balance - Scassa, Teresa (Université d'Ottawa | University of Ottawa, 2005)
In this paper, the author explores the ambiguities and inconsistencies in the Supreme Court of Canada’s latest articulation of the balance to be struck in copyright law. She considers whether the balancing of interests is to be approached by courts based on, or independently of, the balance struck in the legislation. She argues that the identified interests of ‘creators’, ‘users’ and the public should be understood in a textured way, and that the interests of ‘owners’ should neither be forgotten nor conflated with those of creators of works.
Keywords: intellectual property; copyright law; copyright